2015
DOI: 10.1021/nn506599f
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Drug Delivery Nanowafer with Enhanced Therapeutic Efficacy

Abstract: Presently, eye injuries are treated by topical eye drop therapy. Because of the ocular surface barriers, topical eye drops must be applied several times in a day, causing side effects such as glaucoma, cataract, and poor patient compliance. This article presents the development of a nanowafer drug delivery system in which the polymer and the drug work synergistically to elicit an enhanced therapeutic efficacy with negligible adverse immune responses. The nanowafer is a small transparent circular disc that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 39 publications
0
107
0
1
Order By: Relevance
“…Rabbit animal model experiments on rapamycin nanomicellar eye drops revealed a noticeably higher concentration of the drug in the retina. These studies demonstrated that nanomicellar formulation enabled drug delivery to the posterior segment with topical eye drop formulation [11].…”
Section: Nanomicellesmentioning
confidence: 92%
See 3 more Smart Citations
“…Rabbit animal model experiments on rapamycin nanomicellar eye drops revealed a noticeably higher concentration of the drug in the retina. These studies demonstrated that nanomicellar formulation enabled drug delivery to the posterior segment with topical eye drop formulation [11].…”
Section: Nanomicellesmentioning
confidence: 92%
“…Eye drops, although being non-invasive, have shown to have poor drug retention time. It is reported that ≤5% of drug in solution form is absorbed when administered topically [11], therefore the augmentation of this retention time has been widely explored. The lack of bioavailability in the ocular therapeutic treatments is and has been a cause of large concern in the ield of ophthalmology.…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…The nanowafers were fabricated according to a previously published procedure with slight modifications [34][35][36]. A clear CMC solution (4% w/v, 12 mL) was transferred with a pipette onto a polydimethylsiloxane (PDMS) imprint (3″ diameter) containing square posts (of 500 nm × 500 nm, 500 nm high) placed on a flat glass plate and left to dry at room temperature.…”
Section: Nanowafer Fabricationmentioning
confidence: 99%